Comparison of blood pressure in the supine and semi-Fowler\'s position during hemodialysis - Hosein Shahdadi; Seied Reza Mazloum; Mahin Badakhsh; EsmatBandani (Iran University of Medical Sciences, 2010)
ABSTRACT   Background and Aim: Hemodialysis is the most common method of treatment for chronic renal insufficiency an advanced and unretrieveable disorder. Hemodialysis has some complications on which the position of the patient can be effective. Routinely, patients are placed on supine position during hemodialysis, but they are not comfortable in this position, and most of them would like to change their positions to Fowler's position in which the blood pressure may decrease. Placing patients in semi-Fowler's position, if doesn't have any adverse effect on complications, could help patients to be more comfortable during hemodialysis. The aim of this study was to compar blood pressure in the supine and semi-Fowler's position during hemodialysis.   Material and method: In this quasi-experimental study, 45 dialytic patients were selected by purposive sampling. Their blood pressure were measured two times with 30 minutes intervals in both supine and semi-Fowler's positions.   Results: There was no statistical significant difference between two positions in terms of hypotension (p>0.05). The mean systolic blood pressure in supine and Fowler's position were 117.7 and 113.11 mm/Hg, respectively. The mean diastolic blood pressure in supine and Fowler's position were 66 and 65.5 mm/Hg, respectively and there was no statistical significant difference between two positions in terms of diastolic blood pressure.   Conclusion: Regarding the findings it is suggested that patients be placed in either Fowler's or semi-Fowler's position during hemodialysis.